CENSORSHIP AND VIOLATION IN CONTEMPORARY ART (Palíndromo, 2016)
With recent demonstrations of art activists in São Paulo Biennials, we noti- ced greater openness within the cultural institutions for groups of unconventional artists who work not only in the aesthetic field, but also in the political and social. In these fields the influence caused by cases of censorship takes proportions or totally discourage their supporters or even igni- te tempers. This article will address from recent cases where censorship and trans- gression were closely associated with the artistic scope of organized institutions or events the country and as some cases of censorship were the forerunners of cases of transgressions.
Keywords: contemporary art; censorship; transgression